Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Connect with a community of experts ready to provide precise solutions to your questions quickly and accurately. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
[tex]~~~~~~~c = \dfrac{a^2 +3b}{4}\\\\\implies 4c = a^2 +3b\\\\\implies 3b = 4c-a^2\\\\\implies b = \dfrac{4c-a^2}{3}[/tex]
Answer:
b = [tex]\frac{(4c-a^2)}{3}[/tex]
Step-by-step explanation:
[tex]c=\frac{a^{2}+3b }{4}[/tex]
First, let us multiply both sides by 4.
4c = a² + 3b
Now let us take a² to the left side.
4c - a² = 3b
Now to make b as the subject let us divide both sides by 3.
[tex]\frac{(4c-a^2)}{3} =\frac{3b}{3}[/tex]
Therefore,
b = [tex]\frac{(4c-a^2)}{3}[/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.